2018
DOI: 10.1093/ons/opy280
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Robotic Spine Surgery: First Report on Feasibility, Safety, and Learning Curve

Abstract: Background Pedicle screw placement is a commonly performed procedure. Robot-guided screw placement is a recent technological advance that has shown accuracy and reliability with first-generation platforms. Objective To report our initial experience with the safety, feasibility, and learning curve associated with pedicle screw placement utilizing next-generation robotic guidance. Methods A retrospective chart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
111
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(121 citation statements)
references
References 29 publications
2
111
2
Order By: Relevance
“…The learning curve, safety, and feasibility was investigated by Khan et al 18 The authors reported no screw misplacement and no complications within the first 20 patients using the robotic spine surgery system. The mean time for screw insertion was 3.6 minutes, and the authors 18 concluded that only a minimal learning curve exists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The learning curve, safety, and feasibility was investigated by Khan et al 18 The authors reported no screw misplacement and no complications within the first 20 patients using the robotic spine surgery system. The mean time for screw insertion was 3.6 minutes, and the authors 18 concluded that only a minimal learning curve exists.…”
Section: Discussionmentioning
confidence: 99%
“…Urakov et al 17 described improved efficiency with increased case load, but they also noted that the learning curve was largely dependent on the experience and the dedication of the operator. Khan et al, 18 however, described a minimal learning curve involved with robotic spine surgery and stated the efficacy of the technique. Most of the literature describing the learning curve using robotic surgery focused on pedicle screw insertion time but failed to report on the overall operative time, including cases in which the robotic system malfunctioned.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a recent study examining the feasibility of another robotic-navigation guided system, Mazor X (Mazor Robotics Ltd) reported an accuracy rate of 98.7% examining 75 screws. 13 In addition to improving accuracy, while not directly examined in this study, importantly the robotic-navigation system has the added advantage of likely reducing radiation exposure intraoperatively to the both the patient and the surgeon. The only fluoroscopy required intraoperatively are the few images required for registration, including a good AP and lateral at each instrumented level.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, authors reported a favorable learning curve compared to older versions of the system. 32…”
Section: Mazor Xmentioning
confidence: 99%